PENGARUH SELF EFFICACY, POTENSI DIRI, DUKUNGAN ORANG TUA, BIAYA PENDIDIKAN DAN LINGKUNGAN SEKOLAH TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII DI SMAN NEGERI 1 AMPEK NAGARI - Deltia; Eprillison, Vivina; Stevani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The results of the study indicate that: 1) Self-efficacy has a significant effect on the interest in continuing education to college. Which is indicated by a coefficient of 0.213. This coefficient value is significant because t count is 2.658 > t table of 1.665. 2) Self-potential has a significant effect on the interest in continuing education to college. Which is indicated by a coefficient of 0.119. This coefficient value is significant because t count is 2.949 > t table of 1.665. 3) Parental support has a significant effect on the interest in continuing education to college. Which is indicated by a coefficient of 0.386. This coefficient value is significant because t count is 3.396 > t table of 1.665. 4) Education costs have a significant effect on the interest in continuing education to college. Which is indicated by a coefficient of 0.090. This coefficient value is significant because t count is 2.267 > t table of 1.665. 5) The school environment has a significant effect on the interest in continuing education to college. Where indicated by the coefficient of 0.141. This coefficient value is significant because the calculated t of 2.824> ttable of 1.665. 6) Self-efficacy, self-potential, parental support, education costs and school environment together have a significant effect on the interest in continuing education to college. Where the calculated F value is 9.276> Ftable of 2.333 with a significance level of 0.000 <0.05.